The genome sequence of the common alder, Alnus glutinosa (L.) Gaertn. (Betulaceae) [version 1; peer review: 2 approved] - Claudia A. Martin; David G. Bell; Maarten J. M. Christenhusz; Zoë Goodwin (Wellcome Open Research)
We present a genome assembly of a diploid specimen of Alnus glutinosa (the common alder; Streptophyta; Magnoliopsida; Fagales; Betulaceae). The genome sequence has a total length of 456.80 megabases. Most of the assembly is scaffolded into 14 chromosomal pseudomolecules. The mitochondrial genome assemblies have lengths of 505.23 and 155.85 kilobases and the plastid genome is 160.82 kilobases long. Gene annotation of this assembly on Ensembl identified 23,728 protein-coding genes.